OPTIMIZING RISK MANAGEMENT IN IMPLEMENTING THE INDEPENDENT CURRICULUM AT SDN 244 GURUMINDA - Murdani, Rini; Hidayat, Wahyu (INTIHA: Islamic Education Journal, 2024)
Risk management is an effort made to know, analyze, and control risks in various sectors, especially in the education sector. Along with the times, the world is growing and education must also develop so as not to be outdated. The effort made by educational institutions is to change the curriculum to an independent curriculum. However, by having change of the curriculum, there will definitely be risks that must be faced and be able to control it in order to achieve educational goals. This study aims to investigate the role that risk management plays at SDN 244 Guruminda in the implementation of independent curriculum. The research methodology relied on qualitative techniques, using information gathered via interview responses. The results of this study provided information that there are risks in implementing an independent curriculum, both internal risks and external risks. The independent curriculum at SDN 244 Guruminda runs well because the school is able to carry out risk management optimally. This has an impact on improving the quality of schools from ordinary schools to driving schools that are used as examples for other schools.